English Oral Communication Achievement of the Bachelor of Arts Students Major in English for International Communication at Rajamangala University of Technology Lanna, Tak Campus, Thailand - Rechele Ballovar Ella (English Oral Communication Achievement of the Bachelor of Arts Students Major in English for International Communication at Rajamangala University of Technology Lanna, Tak Campus, Thailand, Edition 1, 2024)
Thailand, a country with Thai as its sole official language, mandates English as the first foreign language in its educational curriculum. However, students often face challenges in achieving proficiency in English oral communication due to limited practice opportunities. To address this, Rajamangala University of Technology Lanna (RMUTL) offers the English for International Communication (EIC) program, designed to equip students with essential language and cultural skills for success in various English-related academic and professional fields. The EIC program at RMUTL not only focuses on language proficiency but also emphasizes cultural immersion and practical application. By incorporating interactive activities such as role-playing, group discussions, and presentations, the program aims to create a dynamic learning environment that fosters confidence and fluency in English. Additionally, the curriculum includes exposure to various English-speaking cultures, enhancing students’ intercultural competence and preparing them for global interactions. The program’s holistic approach ensures that students are not only linguistically equipped but also culturally aware, enabling them to navigate and succeed in diverse professional settings. This comprehensive training is crucial for students aspiring to excel in international careers where effective communication is paramount. This study employed a descriptive survey method to investigate the factors influencing English oral communication achievement among students enrolled in the Bachelor of Arts in EIC at RMUTL, Tak Campus. The study included 69 students from the second to fourth year. A researcher-developed questionnaire, validated by three experts and piloted at another university campus, was used to assess reliability and usability. Findings indicated that students generally possess an average level of English oral communication, with room for improvement to meet higher standards. The study also identified aptitude, attitude, and motivation as significant factors impacting students’ oral communication skills. Further research is recommended to explore the specific details of students’ attitudes, aptitudes, and both integrative and instrumental motivations in relation to their oral communication achievements.